EFEKTIVITAS PENDEKATAN STEAM (SCIENCE, TECHNOLOGY, ENGINEERING, ART AND MATHEMATICS) TERHADAP HASIL BELAJAR IPAS KELAS IV SDN 021 SUNGAI KUNJANG - Fathatul Aulia; Muhlis; Rosita Putri Rahmi Haerani (STKIP Subang, 2024)
IPAS outcomes in Class IV SDN 021 Sungai Kunjang are still relatively low. This is caused by learning activities that are not varied, resulting in a lack of student interest in learning and teachers' lack of knowledge about the latest learning approaches and models. This research aims to determine the effectiveness of the STEAM (Science, Technology, Engineering, Art, and Mathematics) approach in improving IPAS learning outcomes for class IV SDN 021 Sungai Kunjang in terms of changes in energy forms. This research is using experimental method. The research design used was a non-equivalent pre test – post test control group design. The instrument is in the form of essay questions. The data analysis techniques in this research are Validity Test, Reliability Test, Normality Test, Homogeneity Test, Hypothesis Test, and N-Gain Test. Based on research results, learning IPAS using the STEAM approach obtained an average score of 85,86, while learning IPAS without using the STEAM approach obtained an average score of 70,93. The results of this research indicate that the STEAM approach is effective in terms of student learning outcomes as evidenced by the results of the independent sample t test, which obtained a sig value. (2-tailed) of 0,001 ˂ 0,05 then H1 is accepted. The level of effectiveness of this research is also proven by the N-Gain test of 0,67 with the criteria being quite effective. So it can be concluded that the STEAM approach is effective in improving IPAS learning outcomes for class IV students at SDN 021 Sungai Kunjang.